Measuring retail service quality: A replication study - Christo Boshoff; Nic S. Terblanché (South African Journal of Business Management, 1997)
In the recent past, few services marketing topics have attracted as much attention as the measuring and management of service quality. In this study an instrument developed in the United States of America, which measures the service quality in a South African retail environment, is empirically evaluated. The retail service quality instrument has been shown to be a valid and reliable instrument and the developers' claim of construct reliability can be supported.
Keywords: 650